Penerapan Metode Electre Pada Studi Kasus Pemilihan Sepeda Motor Matic - Suyibah, Suyibah; Kuzairi, Kuzairi (Universitas Islam Madura, 2022)
The need for transportation is an absolute thing in today's life, almost all people today already have a means of transportation, most of which are motorbikes. With the development of today's technology, motorcycles have made some progress, such as in terms of transmission. For example, on automatic motorbikes whose transmissions are produced manually, there are many variations of automatic motorbikes such as: Beat, Vario, Scoopi and Space. In choosing an automatic motorcycle, of course, consumers want to get the best and right choice. Almost all consumers want automatic motorcycles that are affordable, fuel efficient and comfortable to use. Therefore, we need a decision support system that can assist consumers in choosing the best automatic motorcycle according to consumer desires. This decision support system uses the electre method as a process in determining the best motorbike so that the results are that vario and scoopi dominate more than beat and space.